High-throughput characterization of the effects of H2O vapour on early oxidation across AlxFeyNi1 − x − y composition space. (May 2016) - Payne, Matthew A.; Miller, James B.; Gellman, Andrew J.
Highlights: Al x Fe y Ni1 −  x  −  y ( x  = 0 → 1, y  = 0 → 1 −  x ) oxidation in H2 O/air at 427 °C was studied. The continuous composition boundary of internal/external oxidation was identified. Data were compared with Al x Fe y Ni1− x - y oxidation in dry air at 427 °C. The differences are assessed in terms of a modified Wagner–Maak criterion. Abstract: The presence of H2 O vapour in an oxidizing environment can increase the critical aluminium concentration, N Al *, required to establish a passivating Al2 O3 scale in multicomponent alumina-forming alloys. This work used Al x Fe y Ni1 −  x  −  y composition spread alloy film combinatorial libraries to determine N Al * ( x, y ) continuously across Al x Fe y Ni1 −  x  −  y composition space ( x  = 0 → 1, y  = 0 → [1 − x]) in a 10% H2 O/air mixture at 427 °C. The N Al * ( x, y ) in this environment was significantly higher across much of composition space than that previously measured in dry air. Physical insights from the observed differences are considered using a modified Wagner–Maak model.